A short story of the Phillips curve: from Phillips to Friedman… and back?. (October 2018) - Stirati, Antonella; Meloni, Walter Paternesi
Abstract : A major contribution ofFriedman's 1968 presidential address was the introduction of the long-run vertical Phillips curve. That view, which is consistent with neoclassical foundations, has become so profoundly entrenched in macroeconomists' thinking that increasing evidence of 'hysteresis' has not as yet dislodged it. The prevailing notion of the non-accelerating inflation rate of unemployment (NAIRU) is constructed in terms of the 'natural' unemployment rate, which has allowed for some changes regarding its microeconomic determinants. However, the macroeconomic features of Friedman's natural rate and the NAIRU remain very much the same and unchanged. The blatant path-dependence of empirically estimated NAIRUs creates a dissociation between macroeconomic theory and empirics which, in our view, is unacceptable and demands a change of perspective. Adopting an alternative theory of distribution and employment might rehabilitate the original approach taken by Phillips vis-à-vis Friedman's legacy.